2014
DOI: 10.3109/00365521.2014.915055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bowel preparation on surveillance colonoscopy interval

Abstract: Colonoscopies repeated at interval >3 years showed a significant HR-ADR. The study indicates that a surveillance interval of 3 years can be reasonable for subjects having an index colonoscopy with suboptimal/fair/poor bowel prep and complete colon examination. Colonoscopy should be repeated earlier if symptoms develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…More important than affecting the speed or completion of colonoscopy, poor bowel preparation increases the risk of missed adenomas and CRC. Several studies have also found that the frequency of adenomas detection is greater with high‐quality bowel preparation compared to fair or poor bowel preparation . Flat and depressed lesions carry a higher risk of advanced neoplasm and are thought to progress more swiftly to CRC, and concerningly one study has found the detection of these lesions is significantly less in patients with inadequate bowel preparation …”
Section: Rate Of Adequate Bowel Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…More important than affecting the speed or completion of colonoscopy, poor bowel preparation increases the risk of missed adenomas and CRC. Several studies have also found that the frequency of adenomas detection is greater with high‐quality bowel preparation compared to fair or poor bowel preparation . Flat and depressed lesions carry a higher risk of advanced neoplasm and are thought to progress more swiftly to CRC, and concerningly one study has found the detection of these lesions is significantly less in patients with inadequate bowel preparation …”
Section: Rate Of Adequate Bowel Preparationmentioning
confidence: 99%
“…Several studies have also found that the frequency of adenomas detection is greater with high-quality bowel preparation compared to fair or poor bowel preparation. [19][20][21] Flat and depressed lesions carry a higher risk of advanced neoplasm and are thought to progress more swiftly to CRC, and concerningly one study has found the detection of these lesions is significantly less in patients with inadequate bowel preparation. 22 The quality of the bowel preparation should be assessed at the rectosigmoid junction, and if at this point, it is deemed inadequate the procedure should be aborted.…”
Section: Rate Of Adequate Bowel Preparationmentioning
confidence: 99%
“…Colonoscopies repeated at time interval longer than 3 years showed a significant high-risk adenoma detection rate. Based on these results, they suggest a surveillance interval of no more than 3 years for subjects having an index colonoscopy with suboptimal bowel preparation despite the complete initial colonoscopy [21]. Menees et al reviewed the colonoscopy reports of averagerisk individuals with a normal initial (index) endoscopy.…”
Section: Time Interval Among Screening Colonoscopiesmentioning
confidence: 99%
“…Moreover, two negative examinations for intermediate risk patients require no further follow‐ups. (Cairns et al, ) Finally, one negative examination for high‐risk patients changes the patient category to intermediate risk showed that an increased number of high‐risk adenomas were detected in colonoscopies that are performed more than three years after the initial colonoscopy (Cairns et al, ; Singhal, Virk, Momeni, Krishnaiah, & Anand, ). Currently, the most commonly used colonoscopy technique is white light optical colonoscopy.…”
Section: Introductionmentioning
confidence: 99%